On the role of onshore geostrophic flow on larval retention in a permanent upwelling zone along north-central Chile - Flores, Eduardo A.; Ramos, Marcel; Dewitte, Boris; Astudillo, Orlando; Glasner, Lucas (Frontiers in Marine Science, 2024)
The Humboldt Archipelago (HAp), located off north-central Chile ( 28° - 33° S) is one of the most productive marine zones of the Humboldt Current System (HCS). This area lies within a permanent upwelling zone, characterized by two upwelling centers, 100 km apart, that define the Coquimbo Bays System (CBS). The resulting increase in primary productivity and larval retention are mentioned as the main factors that explain the high biodiversity. However, how these upwelling centers interact remains unclear due to the interplay of various physical features such as the general circulation, the meso- and submeso-scale structures (e.g., eddies), and remote and local forcings (e.g., winds, topography) that affect larval transport in the HAp. In this study, we focus on the role played by geostrophic and Ekman currents in controlling the retention (and dispersion) of particles in these centers based on the analyses of satellite data and hydrodynamic model outputs. Lagrangian models are in particular carried out to document particles’ transport during selected oceanic conditions corresponding to whether Ekman transport or geostrophic recirculation prevails or are debilitated. The latitudinal variation of the Ekman transport reveals two maxima at each upwelling center with differences in spatial extent but not in intensity. Mean zonal geostrophic current occurs in alternating flow at each upwelling center. Results of the Lagrangian experiments highlight the importance of the cross-shore geostrophic flow on larval transport, where an increased transport of particles to the north and northwest occurs at the southern upwelling center, while the northern upwelling center (where HAp is located) received particles from the south and retained particles released in the same area, which is related to the cyclonic geostrophic recirculation and lower Ekman transport. Particle retention increased with depth and under the relaxation and downwelling scenarios revealing the importance of wind alternation for larval retention. The CBS could act as an upwelling shadow in the south and an upwelling trap in the north where the onshore flow of geostrophic current could enhance larval retention and recruitment over longer periods when compared with the Ekman transport timescale.